Predation of Ceraeochrysa cubana (Hagen) (Neuroptera: Chrysopidae) on Hyadaphis foeniculi (Passerini) (Hemiptera: Aphididae) - Moreira, Marciene Dantas; Nunes, Gilmar da Silva [UNESP]; Oliveira, Roberio de; Batista, Jacinto de Luna (Univ Federal Rural Pernambuco, 2019)
This research aimed to evaluate the consumption of Hyadaphis foeniculi by Ceraeochrysa cubana larvae, based on the densities and developmental stages of the prey, as well as the predator searching and handling time, regarding its instar and previous feeding knowledge. In order to evaluate the predation rate, larvae of first, second and third instars of C. cubana were used, which were fed with aphids from first and second instars, from third and fourth instar, and from different instars, at three densities. For searching time and handling evaluation, green lacewing larvae were submitted to different feeding regimens: second instar larvae fed at the first instar with Anagasta kuehniella eggs; second instar larvae, fed at the first instar with H. foeniculi; third instar larvae, fed at the first and second instars with A. kuehniella eggs; third instar larvae, fed at the first instar with the eggs of A. kuehniella and at the second instar with H. foeniculi; third instar larvae, fed at the first and second instars with H. foeniculi. It can be concluded that the daily C. cubana predation rate is influenced by H. foeniculi densities and instars, but the predator searching and handling times are not influenced by the diets provided to them in their previous stages.
Keywords: aphids; consumption rate; fennel; green lacewing